Numerical model of aerodispersed medium containing ice and soot particles for investigation radiant energy extinction - Olga V. Shefer; Viktor A. Sennikov (Известия Томского политехнического университета: Промышленная кибернетика)
A physical-mathematical model of crystal cloud containing ice crystals and soot particles is presented. The numerical model is designed to calculate the extinction factor of visible and IR radiation. Ensembles of spheres, plates, and mixtures of eight types of crystals of symmetrical and asymmetrical shapes are considered as scatterers. The features of spectral behavior of extinction with changes in the microphysical parameters of the medium composed of ensembles of particles of pure ice, amorphous carbon and trioxide dialuminum are demonstrated.